Influence of home/school environments on children's obesity, diet, and physical activity: the SUECO study protocol - Julia Díez; Pedro Gullón; Roberto Valiente; Luis Cereijo; Mario Fontán-Vela; Alba Rapela; Alejandro Blanco; Irene Valero; Agustín Haro; Gema Blasco; José Manuel Díaz-Olalla; Manuel Franco (Elsevier, 2022)
Objective: The SUECO study examines the relationship between urban obesogenic environments and health outcomes among school-age children in the city of Madrid, Spain. We will study how features of the urban environment (related to the food- and the physical activity environment) associate with children's anthropometrics, eating habits, and physical activity levels. Method: We describe the study protocol of this multilevel study in a representative sample of school-age children in the city of Madrid (2017; n = 5,961 children ages 3-12). Main outcome variables include anthropometrics (body mass index, waist circumference, and body fat), healthy and unhealthy consumption measures, and physical activity measures. The primary explanatory variables are grouped into food environment (e.g., unhealthy food retailers' density) and physical activity environment (e.g., walkability, physical activity opportunities) variable categories. Multilevel models will be used to calculate the associations between each indicator and obesity and physical inactivity. Resumen: Objetivo: El estudio SUECO evaluará la relación entre el entorno urbano obesogénico y los resultados en salud en la población infantil escolarizada en Madrid. El estudio explorará cómo influyen las características del entorno urbano (relacionadas con la alimentación y con la actividad física) en las variables antropométricas, los hábitos alimentarios y la actividad física. Método: Se presenta el protocolo de este estudio multinivel, realizado con una muestra representativa de población infantil escolarizada en la ciudad de Madrid (2017; n = 5961 escolares de 3 a 12 años). Las principales variables de resultado incluyen antropometría (índice de masa corporal, circunferencia de cintura y porcentaje de grasa corporal), hábitos alimentarios (saludables y no saludables) y actividad física. Las principales variables independientes son contextuales (del entorno alimentario y del entorno de actividad física). Se utilizarán modelos de regresión multinivel para evaluar las asociaciones entre cada indicador contextual, la obesidad y la inactividad física.